The Braden Scale, A standard tool for assessing pressure ulcer risk, predicts early outcomes after liver transplantation. Issue 9 (September 2017) - Sundaram, Vinay; Lim, Jane; Tholey, Danielle M.; Iriana, Sentia; Kim, Irene; Manne, Vignan; Nissen, Nicholas N.; Klein, Andrew S.; Tran, Tram T.; Ayoub, Walid S.; Schlansky, Barry
Abstract : The Braden Scale is a standardized tool to assess pressure ulcer risk that is reported for all hospitalized patients in the United States per requirements of the Center for Medicare and Medicaid Services. Previous data have shown the Braden Scale can predict both frailty and mortality risk in patients with decompensated cirrhosis. Our aim was to evaluate the association of the Braden Scale score with short‐term outcomes after liver transplantation (LT). We performed a retrospective cohort study of deceased donor LT recipients at 2 centers and categorized them according to the Braden Scale at hospital admission as low (>18), moderate (16‐18), or high risk (<16) for pressure ulcer. We created logistic and Poisson multiple regression models to evaluate the association of Braden Scale category with in‐hospital and 90‐day mortality, length of stay (LOS), nonambulatory status at discharge, and discharge to a rehabilitation facility. Of 341 patients studied, 213 (62.5%) were low risk, 59 (17.3%) were moderate risk, and 69 (20.2%) were high risk. Moderate‐ and high‐risk patients had a greater likelihood for prolonged LOS, nonambulatory status, and discharge to a rehabilitation facility, as compared with low‐risk patients. High‐risk patients additionally had increased risk for in‐hospital and 90‐day mortality after LT. Multiple regression modeling demonstrated that high‐risk Braden Scale score was associated with prolonged LOS (IRR, 1.56; 95% confidence interval [CI], 1.47‐1.65), nonambulatory status at discharge (odds ratio [OR], 4.15; 95% CI, 1.77‐9.71), and discharge to a rehabilitation facility (OR, 5.51; 95% CI, 2.57‐11.80). In conclusion, the Braden Scale, which is currently assessed in all hospitalized patients in the United States, independently predicted early disability‐related outcomes and greater LOS after LT. Liver Transplantation 23 1153–1160 2017 AASLD.